Sipintar: A MOOC-Based Platform to Improve Reading Learning Outcomes - Vendra Ardiansyah; Syukri Hamzah; Agus Trianto (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: This study is motivated by the pressing challenge of improving reading skills among elementary school students in rural areas, particularly in Penukal Utara, where access to quality educational resources is limited. The aim of this research is to assess the effectiveness of the